Improving the Process For the Production of Traditional Bali "Tandusan" Coconut Oil to Extend the Storage of Ecotourism in Family Welfare Program (PKK) Groups Merta Nadi Banjar Lantangidung, Gianyar, Bali - Sudiarta, I Wayan; Setianingsih, Ni Luh Putu Putri; Rustini, Ni Made (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The Community Partnership Program and Traditional Coconut Oil Processing Training "Tandusan" activities will be carried out by Family Welfare Program (PKK) Groups Merta Br. Lantangidung, Batuan, Sukawati, Gianyar, Bali. Based on research, coconut-based oil is a source of medium-chain fatty acids (C8, C10, and C12), which can reach 61.93%. Medium-chain fatty acids have great benefits for human health. Barren coconut oil production in Br. Lantangidung, Sukawati, was done by women. Women's empowerment needs to be continued; this is important because women play a role in increasing resources and empowering the economy in the village. The goal to be achieved is to provide appropriate technology for coconut processing, which has the potential to be widely available in Batuan Village, Sukawati, as "Tandusan" coconut oil for health and consumption. During the hands-on training, additional materials will be provided on packaging technology, production process sanitation and hygiene, and marketing so that the trainees can properly manage their business. The methods used to implement this training are interviews, face-to-face counselling, and direct practice. The output target achieved is that partners know 100% of good processing methods, simple product packaging and labelling, broader marketing, entrepreneurship, and business management.